Pengaruh Kompetensi, Motivasi dan Disiplin Kerja Terhadap Kinerja Karyawan pada Perumda Air Minum Tirta Bumi Serasi Kabupaten Semarang - Shafira Amalia; Kis Indriyaningrum (IPM2KPE, 2023)
This research aims to reveal how strong the influence of competence, motivation and work discipline is on employee performance. The method in this research uses quantitative research methods by collecting primary data directly through distributing questionnaires. The research results show that competence has a negative and insignificant impact on employee performance, and motivation and work discipline have a positive and significant impact on employee performance. In conclusion, this means that if there is a high level of competence, employee performance will decrease. Meanwhile, increasing motivation and work discipline will improve employee performance. Keywords: Work Discipline, Employee Performance, Competence, Motivation